Joint Variation Equations Calculator

varies jointly with and and when
<-- What is given

z varies jointly with y and x, and z = 192 when x = 2 and y = - 6, solve for z when b = 2,c = 3

The statement denotes a relationship of z = kyx where k is a constant
Plugging in our initial statement values of z = 192 when x = 2 and y = - 6, we get:
192 = (2)(-6)k
192 = -12k

Divide each side by -12 to solve for k:
192
-12
=
-12k
-12

k = -16

Solve the second part of the variation equation:
Because we have found our relationship constant k = -16, we form our new variation equation:
z = -16yx

Since we were given that b = 2,c = 3, we have
z = -16 x 2 x 3
z = -96